2011
DOI: 10.1038/ejhg.2011.198
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single-nucleotide polymorphisms in the human holocarboxylase synthetase gene on enzyme catalysis

Abstract: Holocarboxylase synthetase (HLCS) is a biotin protein ligase, which has a pivotal role in biotin-dependent metabolic pathways and epigenetic phenomena in humans. Knockdown of HLCS produces phenotypes such as heat susceptibility and decreased life span in Drosophila melanogaster, whereas knockout of HLCS appears to be embryonic lethal. HLCS comprises 726 amino acids in four domains. More than 2500 single-nucleotide polymorphisms (SNPs) have been identified in human HLCS. Here, we tested the hypotheses that HLCS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The fibroblast K m in their study could not be differentiated from negative controls and the mutant HLCS enzyme was found to have a faster turnover rate than that of the wild-type enzyme (Bailey et al 2008). Other studies have also demonstrated that the L216R mutant has a biotin ligase activity near zero (Esaki et al 2012).…”
Section: Introductionmentioning
confidence: 81%
“…The fibroblast K m in their study could not be differentiated from negative controls and the mutant HLCS enzyme was found to have a faster turnover rate than that of the wild-type enzyme (Bailey et al 2008). Other studies have also demonstrated that the L216R mutant has a biotin ligase activity near zero (Esaki et al 2012).…”
Section: Introductionmentioning
confidence: 81%
“…Full-length human HLCS (NM_000411) was subcloned from plasmid pET41a (+)-HLCS 44 into vector p3XFLAG-CMV-26 (Sigma-Aldrich, Cat# E7283) using NotI and XbaI, thereby creating plasmid FLAG/Myc-HLCS for studies of HLCS overexpression and its effects on H3K9me marks and LTR transcriptional activity. Plasmid pCMV-myc-HLCS was created as described previously 17 and was used for overexpression of Myc-tagged HLCS in co-immunoprecipitation studies.…”
Section: Methodsmentioning
confidence: 99%
“…Unless diagnosed and treated early, HLCS deficiency is uniformly fatal [19]. Single nucleotide polymorphisms in the HLCS gene decrease catalytic activity, but the biological importance of these polymorphisms is unknown [20]. …”
Section: Introductionmentioning
confidence: 99%